An Opinion on Strategic Directions for an Economy in the Capitalist Periphery: The Case of India - Sadri, Sorab (Journal of Economic Development, Environment and People, 2014)
This paper is based on sixteen years of intensive examination and research into three Industrial Sectors (manufacturing, process and technology) of Western India and all observations contained herein are born out of and relate directly to those sectors. The premise upon which we stand is that if business ethics and corporate governance co-exists then with proper HR interventions a value centred corporate culture will very likely emerges and the journey towards achieving organisational excellence becomes that much easier. In the postgraduate textbook entitled Organisational Excellence through Business Ethics and Corporate Governance the authors had begun by defining ethics and stating that ethics was the precondition for generating value centred corporate cultures? They then delved deep into what ethics entrails and how it impacts the organisation as well as the individual within it. Thereafter they went in to the concept of Corporate Governance, defined it, viewed how it developed, examined how it was practiced overseas and then how it came to India. In this paper the authors attempt to show how good governance is based on ethics and how those who head the functions of People Management, Company Secretary, and Accountancy (cost and chartered) can gainfully use it for realising the larger interest of the organisations they belong to. To that extent, this paper is just what the title suggests: an opinion on the subject based on ongoing research